The Political Origin of Pension Funding - Enrico Perotti; Armin Schwienbacher (Tinbergen Institute, 2007)
The paper seeks to explain the huge cross country variation in private pension funding,shaped by historical choice made when universal pension systems were created after theGreat Depression. According to Perotti and von Thadden (2006), large inflationaryshocks due to war damage devastated middle class savings in some countries in the firsthalf of the XX century. This shaped political preferences over the role of capital marketsand social insurance, and contributed to the Great Reversals documented by Rajan andZingales (2003). Wealth distribution shocks are indeed strongly related to private pensionfunding, as a large shock reduces the stock of private retirement assets by 58% of GDP.While the sample size is limited, the results are robust to other explanations, such as legalorigin, original financial development, past and current demographics, religion, electoralvoting rules, redistributive politics, national experiences with financial marketperformance, or other major financial shocks that were not specifically redistributive.Corroborating evidence indicates that such redistributive shocks help explain the crosscountry variation in social expenditures, state ownership of industry, financialdevelopment and employment protection measures as predicted by the political shifthypothesis.
Keywords: J26; G23; G34; G38; 330; Pension system; political economy; wealth distribution; investor protection; retirement finance; Eisenbahnpersonenverkehr; Eisenbahntarif; Fahrplan; Theorie